2018
DOI: 10.1007/s00264-018-3867-1
|View full text |Cite
|
Sign up to set email alerts
|

Do femoral head collapse and the contralateral condition affect patient-reported quality of life and referral pain in patients with osteonecrosis of the femoral head?

Abstract: Collapse of the femoral head and the contralateral condition of ONFH strongly affect patients' activities of daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
1
10
0
2
Order By: Relevance
“…Bilateral hip osteonecrosis is a condition that affects the quality of life [22,23] in patients with osteonecrosis of the femoral head. Males are affected up to three times more than females.…”
Section: Risk Of Collapse and Quality Of Lifementioning
confidence: 99%
“…Bilateral hip osteonecrosis is a condition that affects the quality of life [22,23] in patients with osteonecrosis of the femoral head. Males are affected up to three times more than females.…”
Section: Risk Of Collapse and Quality Of Lifementioning
confidence: 99%
“…In recent years, the use of surgical treatment for elderly patients with ONFH has increased, a result of the incidence of ONFH increasing with the age of the population [18]. Further, the activities of daily living often decrease rapidly with ONFH compared to OA due to collapse of the femoral head [1,2]. Thus, considering the evolution of the surgical technique, it is recommended that the elderly consider THA treatment as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that functional activity is signi cantly impaired in patients with ONFH due to the collapse of the femoral head [19]. Previous reports have demonstrated that both mental state and hip-joint function are similarly impaired in patients with ONFH with progressing collapse of the femoral head [1,2]. Chen et al reported a signi cantly higher prevalence of depression in patients with ONFH than in those with OA [20], and in another study, patients with ONFH had signi cantly lower mental scores after THA than patients with OA [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations